Stress Analysis of Existing Underground Gas Pipeline due to New Road Crossing with ODOL Transportation - Tsamara, Taqiya; Puja, IGN Wiratmaja (UIR PRESS, 2023)
Pipelines are the main choice for transport oil and gas due to its resilience, reliability, safety, and lower cost. Most road crossing pipelines are located underground where protections from the loads can be used such as additional pavement. Underground road crossing pipelines withstand stresses caused by the internal load, earth load, and live load. These loads are affected by the pipe and fluid specifications, soil and environment data, and also the vehicle data. Over dimension and over loading (ODOL) vehicles are a very common problem found in Indonesia. Hence, a stress analysis towards the underground road crossing pipeline being crossed by ODOL vehicles are relevant. A manual calculation of the stress analysis can be done by using API RP 1102: “Steel Pipelines Crossing Railroads and Highways”. A stress analysis using the finite element method (FEM) is conducted using a computer software, namely Abaqus, which also shows the displacement of the pipeline. The case study is an underground road crossing pipeline with depth of 8 feet and uses rigid pavement. The use of rigid pavements over the soil decreases the stress experienced by the pipeline. The results of the total effective stress show a value of 4,785 psi which is still within the allowable range. The stress is found to be directly proportional to the displacement value obtained using FEA. By conducting parametric studies, it is also found that the total effective stress decreases as the burial depth of the pipe is larger.